The dose received by patients during dental X-ray examination and the technical condition of radiological equipment - Marcin Bekas; Krzysztof A. Pachocki (Nofer Institute of Occupational Medicine, 2013)
Background: Implementation of X-ray dental examination is associated with the patient's exposure to ionizing radiation. The size of the exposure depends on the type of medical procedure, the technical condition of the X-ray unit and selected exposure conditions. The aim of this study was to determine the dose received by patients during dental X-ray examination and the assessment of the technical condition of medical equipment. Materials and Methods: The study included a total number of 79 dental X-ray units located in the region of Mazovia. The test methods for the assessment of the technical condition of dental X-ray units and measurement of radiation dose received by patients were based on the procedures elaborated in the Department of Radiation Hygiene and Radiobiology in the National Institute of Public Health - National Institute of Hygiene (Warszawa, Poland) accredited for the certification of compliance with PN-EN 17025. Results: The research found that 69.6% fully meets the criteria set out in the Polish legislation regarding the safe use of ionizing radiation in medicine, while 30.4% did not meet some of them. A tenfold difference in the size of the dose received by patients during dental X-ray examinations was discovered. For example, during a radiography of the canine teeth of a child, the recorded entrance surface dose (ESD) ranged from 72.8 to 2430 μGy with the average value of 689.1 μGy. Cases where the dose reference level defined in Polish legislation of 5 mGy was exceeded were also found. Conclusions: It is essential to constantly monitor the situation regarding the technical condition of X-ray units which affects the size of the population's exposure to ionizing radiation as well as raising dentists' awareness about the effects of X-rays on the human body. Med Pr 2013;64(6):755-759